Combination of Ketorolac Tromethamine and Prednisolone-Loaded PLGA Nanocomposite for Effective Chronic Pain Relief in Mice - Do TN; Liu YC; Chuang YC; Tsai TL; Wu PC (International Journal of Nanomedicine)
Tuyet-Nhi Do,1 Yen-Chin Liu,2– 4 Yu-Che Chuang,5 Tsung-Lin Tsai,1,6,7 Ping-Ching Wu1,6,8– 10 1Department of Biomedical Engineering, College of Engineering, National Cheng Kung University, Tainan, 701, Taiwan; 2School of Post-Baccalaureate, College of Medicine, Kaohsiung Medical University, Kaohsiung, 812, Taiwan; 3Department of Anesthesiology, Kaohsiung Municipal Siaogang Hospital, Kaohsiung Medical University Hospital, Kaohsiung Medical University, Kaohsiung, 812, Taiwan; 4Department of Anesthesiology, National Cheng Kung University Hospital, College of Medicine, National Cheng Kung University, Tainan, 701, Taiwan; 5Department of Pathology and Laboratory Medicine, Taipei Veterans General Hospital, Taipei, 112, Taiwan; 6Center of Applied Nanomedicine, National Cheng Kung University, Tainan, 701, Taiwan; 7Department of Oncology, National Cheng Kung University Hospital, College of Medicine, National Cheng Kung University, Tainan, 701, Taiwan; 8Institute of Oral Medicine and Department of Stomatology, National Cheng Kung University Hospital, College of Medicine, National Cheng Kung University, Tainan, 701, Taiwan; 9Medical Device Innovation Center, Taiwan Innovation Center of Medical Devices and Technology, National Cheng Kung University Hospital, National Cheng Kung University, Tainan, 701, Taiwan; 10University Center of Bioscience and Biotechnology, National Cheng Kung University, Tainan, 701, TaiwanCorrespondence: Ping-Ching Wu, Department of Biomedical Engineering, National Cheng Kung University, Tainan, 701, Taiwan, Email wbcxyz@gmail.com Tsung-Lin Tsai, Department of Oncology, National Cheng Kung University Hospital, College of Medicine, National Cheng Kung University, Tainan, 701, Taiwan, Email sloantsai@mail.ncku.edu.twIntroduction: Chronic pain is a complex condition that requires timely and effective management to prevent long-term emotional, social, and economic consequences. This study aims to develop a poly(lactic-co-glycolic acid) (PLGA)-based nanocomposite co-loaded with ketorolac tromethamine (KT) and prednisolone (PRED) to improve therapeutic efficacy and reduce systemic side effects associated with conventional treatments.Methods: KT-PRED-PLGA nanoparticles were synthesized via a double emulsion method and characterized for their physicochemical properties and biocompatibility. A chronic inflammatory pain model was established in ICR mice using Complete Freund’s Adjuvant (CFA). Mechanical pain thresholds were evaluated using Dixon’s up-and-down method. Histopathological and immunohistochemical analyses were performed to evaluate systemic toxicity and inflammation-related protein expression.Results: The KT-PRED-PLGA nanoparticles exhibited favorable characteristics, including a mean particle size of 166.2 ± 8.0 nm, a polydispersity index of 0.14, a zeta potential of − 15.8 ± 0.3 mV, and encapsulation efficiency exceeding 80%. The nanoparticles sustained drug release up to 92.5% over 120 h. In vitro assays demonstrated the KT-PRED-PLGA nanoparticles revealed high biocompatibility in Vero cells after 72 h of exposure. In vivo experiments demonstrated significantly reduced pain behaviors and tissue inflammation, with minimal toxicity. Behavioral assessments confirmed enhanced analgesic and anti-allodynic effects over the free drugs. Reduced expression of cyclooxygenases (COX-1 and COX-2) and prostaglandin E2 (PGE2) in hind paw tissues confirmed improved anti-inflammatory activity.Conclusion: KT-PRED-PLGA nanoparticles offer safe, sustained analgesia with enhanced therapeutic efficacy and reduced systemic toxicity, highlighting their strong potential for future clinical translation in chronic pain therapy. Keywords: ketorolac tromethamine and prednisolone encapsulation, PLGA nanoparticle drug delivery, nanomedicine, double emulsion strategy, chronic inflammatory pain relief